Cyber Law and Forensics: Unraveling Legal Complexities - Septia, Andien; Phahlevy, Rifqi Ridlo (Proceedings of The ICECRS, 2023)
This data article presents a thorough exploration of the relationship between cyber law and forensics by analyzing a dataset gathered from Lens.org. The study identifies key trends and insights, including the predominant institutions, the increasing scholarly output since 2020, and the most active authors in the field. Notably, the research highlights that the American Board of Legal Medicine is a leading institution in producing cyber law and forensics-related content, with a focus on medicine, as exemplified by the article "Sharp Force Injuries in Clinical Forensic Medicine." Furthermore, Burkhard Madea emerges as the most prolific author, contributing 179 articles, such as "Estimation of the Time Since Death" and "Death Cases Involving New Psychoactive Substances." Additionally, the United States is a major contributor to this discourse with 13,663 articles, primarily published by Elsevier. Among their publications, "Forensic Science International" stands out with 10,135 articles. This data is invaluable for researchers, legal professionals, medical and psychology students, offering insights into the critical field of cyber law and forensics, and its implications in addressing cybercrime. Highlights : In-Depth Analysis: This study employs meticulous keyword analysis to explore the intersection of cyber law and forensics, providing a comprehensive understanding of the relationship between these fields. Insights into Patterns: The research identifies prolific institutions, prevalent fields of study, and key authors, unveiling patterns that enhance our knowledge of scholarly output and contributions in the realm of cyber law and forensics. Global Implications: By emphasizing the ubiquity of forensics in legal domains and its captivating applications, this study underscores its critical role, offering valuable insights for legal practitioners, scholars, and policymakers worldwide. Keywords: Cyber Law, Forensics, Data Analysis, Institutions, Authorship Trends.